Quantification of residual pneumoperitoneum after robotic-assisted laparoscopic surgery. (28th May 2021) - Hefermehl, L; Slieker, J; Lehmann, K; Niemann, T; Maletzki, P; Bujaroska, T; Labulo, O; Li, Z; Guenther, E; Ramakrishnan, V; Kubik-Huch, R; Nocito, A
Abstract: Objective: Laparoscopic surgery improves the postoperative recovery process and relies on CO2 insufflation to establish the operative field. Most residual CO2 is expelled prior to port and incision closure. Computed tomography (CT) is often used to assess an acute abdomen and is highly sensitive in detecting free intra-abdominal air – the hallmark sign of a bowel injury. Yet, the clinical significance of free air in the early postoperative period is confounded by residual CO2 and is not usually due to a visceral injury. The aim of this prospective study was to systematically quantify the residual pneumoperitoneum (RPP) at varying timepoints after robotic-assisted laparoscopic surgery. Methods: Patients undergoing robot-assisted laparoscopic intervention, both radical prostatectomies and left hemicolectomies, were prospectively enrolled in the study. At the conclusion of each operation, manual abdominal pressure was applied to aid in exsufflation of residual CO2. Very-low-dose CT scans were performed on postoperative days (POD) 3, 5, and 7, with subsequent volumetric quantification of RPP. To investigate potential factors influencing the quantity of RPP, correlation plots were made against BMI, age, operative time, total insufflation volume, intra-abdominal pressure, time to flatus and first bowel movement, pain score, and postoperative analgesic requirement. Results: Thirty-one patients undergoing robotic assisted laparoscopic prostatectomy were untill now enrolled in the study, of which only one experienced a Clavien-Dindo 2 complication; all others were free of any complications during post-operative assessment period. On POD3, 5, and 7, 97%, 94%, and 68% of patients, respectively, demonstrated RPP. The RPP volumes were noted to be 9.6 mL (IQR = 3.9-31.8; maximum = 247 mL) on POD3, 1.0 mL (0.1-5.1; maximum = 221 mL) on POD5, and 0.08 mL (1-1.2; maximum = 112 mL) on POD7. A significant correlation was only appreciated between RPP volume and BMI; those with higher BMIs had lower initial volumes of RPP on POD3 and exhibited a more rapid decrease in RPP over one week. Conclusion: One week after robot-assisted laparoscopic operations, a majority of patients will exhibit clinically insignificant RPP, even with volumes as high as 250 mL. Larger patients tend to have smaller residuals of CO2. Our data provide new basic knowledge regarding RPP and may help to interpret postoperative CT-scans.